Limitations of sequence dissimilarity as a predictor of prokaryotic lineage - Alvar A. Lavin; Juan Rivas-Santisteban (Open Biology)
The molecular clock rests upon the assumption that the observed changes among sequences capture the differentiation of lineages, or kinship, as dissimilarity increases with time. Although it has been questioned over the years, this paradigmatic principle continues to underlie the idea that the polymorphic space of a gene is so vast that it is unattainable in evolutionary time. Thus, the molecular clock has been used to obtain taxonomic annotations, proving to be very effective at delivering testable results. In this article, however, we ask how often this assumption leads to inaccuracies when inferring the lineage of prokaryotic genes. Thus, we open an interesting discussion by simulating, in realistic scenarios, the critical times in which specific 5S rRNA sequences of two distant lineages are exhausting the polymorphic space. We contend that certain genes in one lineage will become increasingly similar to those in another over time, as the space for new variants is finite, mimicking phylogenetic features by convergence or by chance, without implying true kinship.